ANALISIS PENGARUH RELATIONSHIP MARKETING TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO BUKU GRAMEDIA PANGKALPINANG - Silalahi, Delpita; Manullang, Rizal Ruben; Medinal (Jurnal Progresif Manajemen Bisnis, 2023)
This research was entitled: “Analisis Pengaruh Relationship Marketing Terhadap Keputusan Pembelian pada Toko Buku Gramedia Pangkalpinang”. This study aims to analyze the effect of relationship marketing (trust, commitment, communication, problem handling) on consumer purchasing decisions at Gramedia bookstores in Pangkalpinang City. This study uses an online survey with a sample of 100 consumers who buy products at Gramedia bookstores. Data were analyzed using multiple linear regression techniques. The study results show that marketing relationships (trust, commitment, communication, problem handling) have a significant effect on consumer purchasing decisions with a tcount value of 3.544 (X1), 3.004 (X2), 0.700 (X3), 3.216 (X3), with a ttable value of 1.984 and a fcount value of 29.216 and ftable 2.47. The level of customer satisfaction and customer loyalty is proven to affect consumer purchase intention. The practical implication of this study is that Gramedia bookstore should improve and maintain good relationships with customers through effective marketing programs to increase consumer purchasing decisions. This study provides important information for Gramedia Book store and other companies that want to understand the factors that influence purchasing decisions.